Impact of Reinsurance on Performance of Nepalese Insurance Companies - Maharjan, Rajendra (Nepalese Journal of Management Science and Research, 2019)
Reinsurance is considered as backbone of the insurance industry in developed and developing countries as it indirectly injects capital and Nepalese insurance companies are no exception. Thus, this study is aims to find out whether the use of reinsurance arrangement lead to positive effect or not? Three portfolios have been formed life, nonlife and industry. The study used 11 years unbalanced cross sectional secondary data from 2007/08 to 2017/18. The sample of the study consists of seven from life and nine from nonlife with 138 firm years’ observations. The dependent variable performance is measured by profitability (ROA and ROE) and solvency while reinsurance ceded as explanatory variable. Capital employed and size of the firm are considered as control variables. The study employed descriptive cum causal comparative research design. Regression analysis has been performed to see the effect of reinsurance on firm performance.The result depicts that reinsurance has a positive and significant impact on performance of insurance companies. This finding indicates that reinsurance improves the cost efficiency of primary insurers. Further, reinsurance is a complement for capital in order to enhance solvency while negative relation indicating solvency of the insurers increases with the level of used reinsurance, to the extent that reinsurance and capital can be substitutes of each other. Thus, this study concludes that primary insurers can benefit from reinsurance as its relief on capital, diversify risk and in turn helps to earn profitability by sharing the risk with reinsurers.